I would like to understand how would the original identity of $$ \sin^2 \theta + \cos^2 \theta = 1$$ derives into

$$ 1 + \cot^2 \theta = \csc^2 \theta $$

This is my working:

a) $$ \frac{\sin^2 \theta}{ \sin^2 \theta } + \frac{\cos^2 \theta }{ \sin^2 \theta }= \frac 1 { \sin^2 \theta } $$

b) $$1 + \cot^2 \theta = \csc^2 \theta $$ How did the $ \tan^2 \theta + 1 = \sec^2 \theta$ comes into the picture?

enter image description here

enter image description here


The same way; you start with $\sin^2\theta + \cos^2\theta = 1$ and divide both sides by $\cos^2\theta$.

  • $\begingroup$ Ok, I got confused when the professor mentioned that we can derive the following result by dividing by sin^2 theta. He brought the tan^2 theta equation from the previous lecture. $\endgroup$ – ilovetolearn Jul 15 '17 at 3:55

It is taken from Pythagoras theorem, Let Know that let

c= Hypothenuse

a= Opposite


length of the triangle can be found by


Now divide everything by b

We have


Notice that

$$tan \theta=\frac{a}{b}$$

$$sec \theta=\frac{1}{\cos \theta}=\frac{c}{b}$$

There you go

$$1+\tan^2 \theta=\sec^2 \theta$$

There rest of the two identities are obtained by dividing c&a!

Which is Division by c $$\sin^2 \theta+\cos^2 \theta=1$$

Division by a



Take the original pythagorean identity, and divide by $\sin^2 x$ to get one of the identites, and divide by $\cos^2 x$ for the other.


Just as you divide $\sin^2(\theta)+\cos^2(\theta)=1$ by $\sin^2(\theta)$ to get $ 1 + \cot^2 (\theta) = \csc^2 (\theta)$,

you can divide $\sin^2(\theta)+\cos^2(\theta)=1$ by $\cos^2(\theta)$ to get $\tan^2 (\theta) + 1 = \sec^2(\theta)$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.